Dynamic of boron in forest ecosystems traced by its isotopes: A modeling approach - Chetelat, Benjamin; Gaillardet, Jérôme; Chen, JiuBin (Chemical geology, 2021)
Understanding the factors that control the cycling of nutrients in terrestrial ecosystems and in the Critical Zone is of fundamental importance given its role for example in nutrient availability to sustain forest productivity, and ultimately in soil carbon storage. In this paper, we developed a model to assess the dynamic of boron in forest ecosystems and to appraise how the impacts on boron cycling by internal or external factors should be reflected in the changes of its isotopic compositions across an ecosystem. Despite the scarcity of data, we tested this model on two case studies and were able to reproduce the distribution of boron isotopes between the different pools of these two contrasted ecosystems. The model shows a time dependency of the boron isotopic composition of the different biotic and abiotic compartments of the ecosystem. When the forest grows, a transient enrichment in the heavy isotope up to 20‰ relative to the values at steady-state is observed in the biomass and the soil solutions. The magnitude of this enrichment, and the return time to steady state, are sensitive to B supply and plant demand for boron. We also tested the responses of B dynamic to natural or anthropogenic disturbances and we show that they are well reflected in the variations of the B isotopic compositions of the different pools. As a whole, we show that B isotopes are a good potential tracer of nutrient cycling and by extension, a promising proxy for tracing the global functioning of terrestrial biosphere at present and in the past. •We developed a model to assess the dynamic of boron and its isotopes in forest ecosystems.•The δ11B values of the ecosystem’s compartments reflect the responses of B dynamic to natural and anthropogenic forcings.•B isotopes reveal a potential tracer of nutrient cycling and proxy for tracing the functioning of the terrestrial biosphere.